(untitled) (Journal of the College of Basic Education, 2025)
The present study aims to identify the level of auditory perception among children with cochlear implants in institutes for the hearing impaired. It also seeks to explore differences in auditory perception based on gender (male, female) and chronological age (8, 9, and 10 years). A stratified random sample (equal distribution method) of (120) children with cochlear implants was selected from both public and private institutes for the hearing impaired affiliated with the Ministry of Labor and Social Affairs in the governorates of (Baghdad, Babylon, and Najaf). The researchers developed and applied an auditory perception scale after following all scientific procedures, resulting in a final version consisting of 30 items. The results showed a generally low level of auditory perception among the sample of children with cochlear implants. The sample exhibited the same level of auditory perception regardless of gender, while the level was affected by chronological age. Conclusions: Children with cochlear implants suffer from weakness or deficiency in auditory perception. Recommendations: Government institutions should pay attention to children with cochlear implants by establishing specialized centers for their training and education, as researchers observed that most of the centers that cater to these children are non-governmental institutions. Suggestions: Conduct a similar study to the current research on other samples of children, such as those with hearing impairments and typical hearing.